Effectiveness of blood flow restriction versus traditional weight-bearing training in rehabilitation of knee osteoarthritis patients with MASLD: a multicenter randomized controlled trial - Hu, Chengfang; Zhu, Bin; Wang, Yanmao; Yang, Fei; Zhang, Jun; Zhong, Wanrun; Lu, Shengdi; Luo, Congfeng (Frontiers in Endocrinology, 2023)
To compare the reliability and effectiveness of blood blow restriction resistance training (BFR) versus traditional weight-bearing training (WB) in knee osteoarthritis (KOA) patients with metabolic dysfunction-associated steatotic liver disease (MASLD). Methods: This multicenter randomized controlled trial was conducted from January 2021 to June 2022 at Shanghai Jiao Tong University affiliated Sixth People's Hospital and The People's Hospital of Mengla County. A total of 120 outpatients were recruited and randomized to perform WB (n=60) or BFR (n=60) resistance training protocols in accordance with standard recommended protocols for 12 weeks. Demographic data and Kellgren and Lawrence grading system scores were collected. Pain, range of motion (ROM), scaled maximal isotonic strength (10RM), selfreported function (KOOS), and 30-s chair sit-to-stand test results were assessed at weeks 1, 4, and 12. Results: 112 patients (57 in the WB group, 55 in the BFR group) completed the training programs and assessments. No significant intergroup demographic differences were noted. ROM and scaled 10RM significantly increased at the 4-and 12-week assessments and differed significantly between groups. The pain, ability of daily living and quality of life subscale in KOOS increased significantly at the 12week assessment and differed significantly between groups, adjusted for baseline value. Significant and comparable increases in 30-s chair sit-to-stand test results were observed within and between study groups. Conclusions: BFR training enhanced muscle strength, reduced pain, and improved daily living and sports activities in patients with KOA, compared to WB training alone. BFR should be recommended for rehabilitation in KOA individuals with MASLD.